The Incredible Lightness of Being Methane-Fuelled: Stable Isotopes Reveal Alternative Energy Pathways in Aquatic Ecosystems and Beyond - Grey, Jonathan (Frontiers in Ecology and Evolution, 2016)
We have known about the processes of methanogenesis and methanotrophy for over 100 years, since the days of Winogradsky, yet their contributions to the carbon cycle were deemed to be of negligible importance for the majority of that period. It is only in the last two decades that methane has been appreciated for its role in the global carbon cycle, and stable isotopes have come to the forefront as tools for identifying and tracking the fate of methane-derived carbon within food webs, especially within aquatic ecosystems. While it is not surprising that chemosynthetic processes dominate and contribute almost 100% to the biomass of organisms residing within extreme habitats like deep ocean hydrothermal vents and seeps, way below the reach of photosynthetically active radiation, it is perhaps counterintuitive to find reliance upon methane-derived carbon in shallow, well-lit, well-oxygenated streams. Yet, apparently, methane-derived carbon contributes to varying degrees across the spectrum from point sources to extremely diffuse sources. Certainly a good proportion of the evidence for methane-derived carbon contributing to freshwater food webs comes from somewhere in the middle of that spectrum; from studies of seasonally stratifying lakes (mono- or dimictic) wherein, there is a defined gradient or boundary at which anoxic meet oxic conditions and consequently allows for close coupling of methanogenesis and methanotrophy. However, even seemingly well-mixed (polymictic) lakes have a contribution of methane-derived carbon contributing to the benthic biomass, despite an almost continual supply of photosynthetic carbon being delivered from the surface. Aside from the fundamental importance of identifying the carbon sources fuelling biomass production, stable isotopes have been integral in the tool box of palaeolimnologists seeking to identify how contributions from methane have waxed and waned over time. Here, we synthesise the current state of knowledge in the use of stable isotopes to trace methane-derived carbon in primarily freshwater ecosystems.